Complete Flags of the World - Barker, Brian Johnson; DK Publishing, Inc. (London ; New Holland, 2009)
Presents the history and symbolic interpretation of every national flag and includes the flags of international organizations and of each state of the United States.
Rev. ed. of: Ultimate pocket flags of the world. 1997.
Colored maps of the world, Europe, and the Caribbean on endpapers.
Includes index.
Keywords: Flags -- Handbooks, manuals, etc; National emblems -- Handbooks, manuals, etc